PENGARUH GAYA KEPEMIMPINAN, BUDAYA KERJA ORGANISASI, KOMPETENSI PEGAWAI, TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI INTERVENING DI BADAN PUSAT STATISTIK - Pramaika Yoga Sentani; Kamaruzzaman Onaning; Suryati Veronika (JURNAL ILMIAH BISNIS, PASAR MODAL DAN UMKM, 2020)
The propose of this study is to examine and analyze the influence of leadership style, organization culture, competence, to employee performance, and to examine and analyze the influence of leadership style, organization culture, competence, to employee performance with work motivation as intervening variable. 100 respondent is spread in head office of central agency of statistic.This study is quantitative characteristic with smartPLS as an analysis method. The result showed that competence directly influence to employee performance, while leadership style, and organization culture uninfulenced to employee performance. Organization culture through work motivation influence to employe performance, while leadership style and competence through work motivation are uninfluenced to employee performance